IMPLEMENTASI ATAS KEWENANGAN KALAPAS DALAM MELAKSANAKAN PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A BOJONEGORO - Ummah, Maslakhatul Laila; Astuti, Pudji (Universitas Negeri Surabaya, 2021)
Penitentiary is the final stage of the criminal justice system. Various cases of violations occur ranging from the mild to the most severe such as riots,bribes against law enforcement officials to obtain the desired facilities and desires, up to the Lapas burning case. This study aims to determine the implementation of the authority of Kalapas as well as the obstacles in carrying out fostering prisoners in Penitentiary in Bojonegoro. This research uses the type of sociological legal research. Data collection techniques used were interviews with the Head of the Bojonegoro Correctional Institution, Penitentiary Officers invited, as well as prisoners in Penitentiary Bojonegoro. Data analysis techniques in this study used qualitative analysis of the data in this study instead of numerical information. The results showed that in carrying out prisoners' training there was a prisoner training process which was divided into 4 stages, namely the first stage was called the admission and orientation phase, an introduction to prisoners, the second phase after the prisoners served 1/3 of their criminal period, the third stage if the results of the evaluation of the TPP session state that the prisoner has undergone the previous stages of coaching well he can continue the third stage of coaching, prisoners can continue coaching in the fourth stage. Obstacles in carrying out the formation of prisoners in Class II A Penitentiary in Bojonegoro can be seen from the inadequate facilities or supporting facilities, the lack of law enforcement factors compared to the large number of prisoners.